Longevity, aging and rapamycin - Ehninger, Dan (Springer Basel, 2014)
The federal drug administration (FDA)-approved compound rapamycin was the first pharmacological agent shown to extend maximal lifespan in both genders in a mammalian species. A major question then is whether the drug slows mammalian aging or if it has isolated effects on longevity by suppressing cancers, the main cause of death in many mouse strains. Here, we review what is currently known about the effects that pharmacological or genetic mammalian target of rapamycin (mTOR) inhibition have on mammalian aging and longevity. Currently available evidence seems to best fit a model, wherein rapamycin extends lifespan by suppressing cancers. In addition the drug has symptomatic effects on some aging traits, such as age-related cognitive impairments.